131I INTERNAL CONTAMINATION AND COMMITTED DOSE ASSESSMENT AMONG NUCLEAR MEDICINE MEDICAL PERSONNEL. Issue 3 (11th December 2017) - Brudecki, K; Kluczewska-Gałka, A; Mróz, T; Jarząb, B; Zagrodzki, P; Janowski, P
Abstract: This study presents 131 I thyroid activity measurements of 56 employees of the Department of Nuclear Medicine and Endocrine Oncology, Centre for Oncology in Gliwice. The research instrument was a whole-body spectrometer. In 44 out of 56 examined staff members, the determined 131 I activity was found to be above the detection limit. The measured activities ranged from 6 ± 2 to 457 ± 118 Bq. The maximum estimated committed effective dose reached was 1.5 mSv/y. The results were compared with previous measurements conducted in another Polish nuclear medical unit. From this comparison, we can see that radiological safety among nuclear medicine personnel can be improved by appropriate work organisation. Reducing exposure of workers can be achieved by properly organised turnovers concerning the most vulnerable worksites. In addition, to lower the radiation risk, it is essential to comply strictly with the isolation regime for the patients.